2021
DOI: 10.1111/febs.16097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ligand binding and resulting conformational changes in pyrophosphatase NUDT9

Abstract: Nudix hydrolase 9 (NUDT9) is a member of the nucleoside linked to another moiety X (NUDIX) protein superfamily, which hydrolyses a broad spectrum of organic pyrophosphates from metabolic processes. ADP-ribose (ADPR) has been the only known endogenous substrate accepted by NUDT9 so far. The Ca 2+ -permeable transient receptor potential melastatin subfamily 2 (TRPM2) channel contains a homologous NUDT9-homology (NUDT9H) domain and is activated by ADPR. Sustained Ca 2+ influx via ADPR-activated TRPM2 triggers apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…NUDT9 plays a role in breast cancer [39]. The NUDT9 protein can dock with ADPR, and 218 amino acids directly participate in the docking [40]. We simulated the docking and found that the goose NUDT9 protein could dock with ADPR.…”
Section: Discussionmentioning
confidence: 99%
“…NUDT9 plays a role in breast cancer [39]. The NUDT9 protein can dock with ADPR, and 218 amino acids directly participate in the docking [40]. We simulated the docking and found that the goose NUDT9 protein could dock with ADPR.…”
Section: Discussionmentioning
confidence: 99%
“…hsTRPM2), but here the preceding tetramerization step of the NUDT9H domains is absent (Huang et al, 2023). For the human NUDT9 enzyme a monomeric form of organization is assumed (Shen et al, 2003;Perraud et al, 2003;Gattkowski et al, 2021). Since the short stretch of amino acid residues critical for tetramerization of NUDT9H is absent in modern TRPM2 variants (Huang et al, 2023), it can be expected that our separately expressed hsNUDT9H domain also interacts as a monomer (Gattkowski et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…6; Fig. 1c), whereas ADPR hydrolysis in NUDT9-H occurs only in the presence of Mg 2+ but not Ca 2+ (ref 10,20 ). By contrast, vertebrate TRPM2 opens only in the presence of Ca 2+ with a lower open probability 21 , and cannot hydrolyze ADPR 22 .…”
Section: The Trpm2 Chanzyme Is Regulated By Five Ligand Binding Sitesmentioning
confidence: 94%